Persistence, Prevalence and Antibiotic Susceptibility of Pseudomonas aeruginosa Isolated from Hospital Wastewater. - Daniel Abbey; Adamu Hafsa Abdullahi (International Journal of Advanced Health Science and Technology, 2025)
The increasing prevalence of antibiotic-resistant bacteria in hospital wastewater poses significant public health risks. This study investigates the persistence, prevalence, and antibiotic susceptibility of Pseudomonas aeruginosa in hospital wastewater collected from three healthcare facilities in Dutse, Jigawa State, Nigeria: Rasheed Shekoni Teaching Hospital, Dr. Sambo Hospital, and Dutse General Hospital. Wastewater samples were analyzed for bacterial isolation, characterization, and antibiotic susceptibility. Wastewater samples were analyzed for bacterial isolation, characterization, and antibiotic susceptibility. Results showed that P. aeruginosa was just present everywhere in samples collected from Dr. Sambo Hospital and Dutse General Hospital. But at Rasheed Shekoni Teaching Hospital prevalence was a bit lower, at 60%. Physiochemical analysis showed that P. aeruginosa exhibited optimal growth at 37°C with pH variations influencing its persistence. The bacterium sticks around for up to 72 hours floating around in wastewater and hospital water runoffs. Yes, this shows just how tough this microbe can be. Antibiotic susceptibility testing indicated high resistance to multiple antibiotics, with no zones of inhibition observed for several drugs, including ampicillin, streptomycin, and nalidixic acid. However, some isolates showed susceptibility to ciprofloxacin and gentamycin. The findings underscore the urgent need for improved hospital wastewater treatment to mitigate the spread of antibiotic-resistant bacteria in the environment. Future scientific research should dive into the mechanisms at the molecular level that drive resistance from microorganisms found in wastewater from hospitals.